FAKTOR-FAKTOR YANG MEMPENGARUHI TAXPAYER COMPLIANCE DALAM MEMBAYAR PROPERTY TAX DI KECAMATAN LENEK KABUPATEN LOMBOK TIMUR TAHUN 2021 - Siti Reuni Inayati; Rana Syarif Hidayat; Ikhwan Wadi; Ahmad Murad (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2023)
This study aims to examine the variables that affect taxpayer compliance. The variables in this study consisted of 2 (two) independent variables, namely awareness (X1), knowledge (X2) and the dependent variable, namely taxpayer compliance (Y). Data were obtained by distributing questionnaires that were distributed as many as (100), questionnaires that could not be processed as many as (7), questionnaires that did not return (-), damaged questionnaires as many as (-), and questionnaires that could be processed as many as (93). Data were analyzed using multiple regression analysis. The results of this study indicate that the variables of awareness and knowledge of taxpayers have no significant effect on taxpayer compliance.